Social insurance and allied services : memorandum on the Beveridge Report
1943-02-10 1943 1940s 24 pages 23. on industry, bring about the very unemployment which it is the desire of everyone to avoid, that we have come to the following conclusions. V. CONCLUSIONS: (68) The Abolition of Want, which is the first objective of the "Beveridge" Report, must, in our view, hold one of the highest places in the order of priority of this country's post-war obligations. We therefore think that the Government should forthwith determine the extent of that Want and consider the best methods for removing it, and submits its proposals to Parliament which is the supreme authority. (69) Before committing the country to the second objective of the "Beveridge" proposals relative to those not in Want, the Government should establish an order of priority of the country's post-war obligations and programmes as a whole and, having regard to the possible post-war industrial performance of this country, so allot our available resources as to see that justice is done to all and injustice to none. (70) In so far as it may be necessary to set up any further Committees on this subject, we trust that the Employers and Workers, as two of the contributors to the existing Social Service Insurance system, will be included in the membership of these Committees. 200/B/3/2/C216/5/50